Societal Factors and Life Satisfaction: Evidence from Low Income Urban Societies in a Developing Country - Mafini, Chengedzai; Meyer, Daniel (Journal of Economics and Behavioral Studies, 2016)
This paper tested the influence of four societal factors, namely marital status, religion, age and gender on the life satisfaction of low income urban earners in a developing country. A survey was conducted using a sample consisting of 985 individuals drawn from three low income townships in Gauteng Province, South Africa. In order to measure life satisfaction the validated Satisfaction with Life Scale developed by Diener et al. (1985), was utilised. Associations between each societal factor and life satisfaction were tested using multiple regression analysis. Marital status was statistically insignificant (Î²=0.058; P=0.170). All categories of religion were statistically significant, with Christianity (Î²=0.424; P=0.044) exerting the highest influence on life satisfaction. In terms of age, young adults demonstrated higher satisfaction with life than older adults, with young adults (Î²=0.369; P=0.019) exerting the highest influence on life satisfaction than other age categories. Gender was statistically insignificant (Î²=0.059; P=0.307) depicting that life satisfaction is not dependent on gender. The paper closes by drawing conclusions based on the results and suggesting several policy implications for improving the impact of each societal factor on life satisfaction.